Proceedings of the 4th International Conference on Wireless Mobile Communication and Healthcare - "Transforming Healthcare Thro 2014
DOI: 10.4108/icst.mobihealth.2014.257232
|View full text |Cite
|
Sign up to set email alerts
|

Using FHIR to develop a healthcare mobile application

Abstract: Health care domain have attracted considerable amount of research fields. One of the field that has a drastic focus on health care domain is data mining. Mainly health care system focuses on some data mining theories like classification, clustering etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…We obtained 11 categories for FHIR implementation. From a platform point of view, we considered the implementation of mobile/tablet apps [ 3 , 9 , 28 , 35 , 39 , 51 , 57 , 60 , 65 , 70 , 72 , 77 , 82 ], standalone apps/servers [ 3 , 23 , 51 , 58 , 61 ], web services/API [ 3 , 11 , 14 , 26 , 34 , 36 , 40 , 48 , 53 , 56 , 71 , 78 ], and web-based tools/applications [ 18 , 26 , 37 , 40 , 42 , 46 , 55 , 69 , 78 ] categories. From a conceptual framework, we considered the categories of general FHIR implementation [ 48 , 59 ], using SMART on FHIR [ 3 , 14 , 22 , 31 ], HL7 API (HAPI)-FHIR server/library/applications [ 14 , 16 , 20 , 32 , 34 - 36 , 40 , 43 , 51 , 54 , 55 , 73 , 76 , 81 , 82 ], and FHIR general framework [ 14 , 40 ,…”
Section: Resultsmentioning
confidence: 99%
“…We obtained 11 categories for FHIR implementation. From a platform point of view, we considered the implementation of mobile/tablet apps [ 3 , 9 , 28 , 35 , 39 , 51 , 57 , 60 , 65 , 70 , 72 , 77 , 82 ], standalone apps/servers [ 3 , 23 , 51 , 58 , 61 ], web services/API [ 3 , 11 , 14 , 26 , 34 , 36 , 40 , 48 , 53 , 56 , 71 , 78 ], and web-based tools/applications [ 18 , 26 , 37 , 40 , 42 , 46 , 55 , 69 , 78 ] categories. From a conceptual framework, we considered the categories of general FHIR implementation [ 48 , 59 ], using SMART on FHIR [ 3 , 14 , 22 , 31 ], HL7 API (HAPI)-FHIR server/library/applications [ 14 , 16 , 20 , 32 , 34 - 36 , 40 , 43 , 51 , 54 , 55 , 73 , 76 , 81 , 82 ], and FHIR general framework [ 14 , 40 ,…”
Section: Resultsmentioning
confidence: 99%
“…HL7 FHIR is an emerging standard that is rapidly gaining attention and being adopted by the health information technology industry and health care organizations [ 15 ]. This standard implements various types of information generated in the clinical environment in the form of a resource for exchanging clinical data and, thus, it ensures interoperability.…”
Section: Methodsmentioning
confidence: 99%
“…FHIR is a standard that focuses on providing a secure interoperability environment for health service providers to exchange data using the Representational State Transfer (REST) API [ 15 , 17 , 18 ]. We built a repository with the FHIR server that applied the STU3 (Standard Trial Use 3) version of FHIR to provide create , read , and delete operations for resources (Observation, Sequence) containing genome analysis result information.…”
Section: Methodsmentioning
confidence: 99%
“…Nine criteria were used in reviewing each system namely database, multiple users, communication, notifications, data sharing, flexible scheduling, community type, visual aids and statistics and charts. AidIT was the only system identified that provides data storage and access and is a mobile EMR system that allows patients to manage their records and facilitates the exchange of these records between patients and practitioners [8]. The AidIT system provides patients with a personal health folder that organises a patient's data into five separate categories namely: the patient's personal information (e.g.…”
Section: System and Data Requirementsmentioning
confidence: 99%